Scenario-based planning for a dynamic tourism system with carbon footprint analysis: A case study of Xingwen Global Geopark, China. (1st May 2020) - Luo, Yuyan; Mou, Yu; Wang, Zhong; Su, Zerui; Qin, Yong
Abstract: Since the concept of low-carbon has been incorporated in all aspects, low-carbon tourism, as one of the vital branches of low-carbon economy, has grasped much attention from researchers. Under the current trends, the actual emissions of greenhouse gas will be doubled the planned target in the future, which are obviously overlooked by the tourism industry. In terms of carbon footprint measurement, this paper proposes a multi-dimensional model with four low-carbon sub-systems including economy, environment, control and management and selects Xingwen Global Geopark as the sample in the scenario-based planning. Inspired by the idea of responsible tourism, this paper applies dynamic model in measuring carbon footprint, so as to provide future policy implications for geoparks. Through the scenario-based prediction of carbon footprint in Xingwen Global Geopark, we found it has experienced a constant promotion in low-carbon development with increasing carbon footprint but decreasing carbon intensity; the booming of tourists may bring worsen carbon footprint, slow-paced increase of tourists but poorer low-carbonization will possibly result in high carbon intensity; the current path is not the best and not conducive for middle and later period before 2030; the results of scenario analysis indicate that the win-win development can only be achieved through the low-carbon construction of scenic spots. Graphical abstract: Image 101797 Highlights: A conceptual logical DPSIRM framework is developed for low-carbon tourism system. Traditional static measurement for tourism-related carbon footprint is transformed into dynamic measurement. Carbon footprint of key elements in tourism is dynamically illustrated under different scenarios. Responsible tourism is introduced to enrich the perspective of scenario planning analysis.